KUALITAS FISIK DAN PH JERAMI PADI YANG DIFERMENTASI MENGGUNAKAN BAL DENGAN BERBAGAI LEVEL BEKATUL - akbar, mishbahulakbar; Rico anggriawan; Diyah Ayu Candra (Universitas Islam Balitar, 2025)
This study aims to determine the effect of adding rice bran levels on physical quality (color, aroma, texture and presence of fungi) and pH in rice straw fermentation using LAB. The study was conducted in Blitar with materials in the form of rice straw, rice bran, probiotics (LAB), molasses and water. The tools used in this study were digital scales, ropes, plastic bags, vacuum pumps and pH meters. The research design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The treatments tried in this study were P0 = Rice Straw + Probiotics + 0% Rice Bran, P1 = Rice Straw + Probiotics + 5% Rice Bran, P2 = Rice Straw + Probiotics + 10% Rice Bran, P3 = Rice Straw + Probiotics + 15% Rice Bran. The variables measured in this study were color, aroma, texture, presence of fungi and pH. The results showed that the addition of rice bran had no significant effect (P>0.05) on physical quality but a very significant effect (P<0.01) on fermentation pH. The conclusion of this study is that the addition of rice bran to straw fermentation had no significant effect on organoleptic performance. A significant decrease in fermentation pH indicated that fermentation was progressing well. The addition of 10% rice bran had the best results in terms of organoleptic and pH.